Water, Well-Being, and the Prosperity of Future Generations - Chase, Claire (World Bank, Washington, DC, 2017)
Water-related diseases are a major health burden for populations, especially the poor. Meeting global aspirations for poverty reduction will require addressing the global water and sanitation challenge. This discussion paper provides an overview of the poverty-related impacts of inadequate water supply and sanitation services, and highlights the new policy challenges that have emerged in a more populated, polluted, and urbanized world with finite water resources. New approaches that assure sustained changes in individual behavior, more equitable access to services, and incentives for improved water resource stewardship are needed.